The Effectiveness Of Knowledge-Based Economy On China's Economic Growth - Sinaga, Dearlina; Manullang, Marihot (PT Inovasi Pratama Internasional, 2025)
This study aims to discuss the Effectiveness of Knowledge-Based Economy on China's Economic Growth. The research design used is quantitative correlation where this study is a study that investigates the extent to which variations in a factor are related to variations in one or more other factors based on the correlation coefficient, while what is meant by quantitative research is research where the data used is in the form of numbers. In this knowledge era, the potential of natural resources owned by a country does not guarantee a country is able to develop and grow the economy sustainably, in this case many developed countries also implement a knowledge-based economy, especially China where China is able to implement a knowledge-based economy and can be declared successful and able to grow its economic growth well, when compared to countries that follow the basics of a knowledge-based economy. China in its level of development which is none other than implementing the concept of a knowledge-based economy can be called successful by looking at the level of economic growth which every year shows increasingly positive results where the growth is 10% growth. In the 1980s when China was still experiencing a political dilemma of the state by adopting a socialist stream that still could not develop well, but when the change of leadership and the change of stream where the stream adopted was capitalism showed drastic changes.